KANIBALISME PARTAI POLITIK ISLAM DI KOTA SURABAYA PADA PEMILU 2014 - Palestina, Firdaus Ayu (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2015)
The focus of this paper is the phenomenon of the decline of votes at every election as well as the causes of cannibalism that occurred between Islamic parties in the 2014 elections. In this thesis uses qualitative research with descriptive research method. The results of this thesis study is known that the cause of the decline of Islamic party; Fusion and the history that accompanied political parties. Factors Islamic party of the less successful